Hopeful employees - Czukor, Gergely (Psihološka obzorja (Ljubljana), 2024)
This study investigated the concurrent validity of an employee-organization fit measure based on societal development aims to forecast employee hope in successful work outcomes via enhancing perceived task significance. White-collar employees from various roles and sectors of professional organizations in Turkey participated in this survey study. A subjective fit index was computed based on ratings of the extent participants preferred 26 development aims and the extent they perceived their organizations incorporated those goals into their agenda. Validity was confirmed in binary correlations of fit with hope and task significance and polynomial regressions on hope. The mediating role of task significance was confirmed in the relationship between employee-organization fit and hope. Direct involvement as a moderator was not significant. The research expands fit dimensions with a validated measure of societal development that aims to measure and incorporate hope, positive psychology, and employee-level corporate social responsibility outcomes.
Keywords: cilji družbenega razvoja; employee hope; employee-organization fit; personnel; pomembnost naloge; societal development aims; task significance; ujemanje zaposlenega in organizacije; upanje zaposlenih; zaposleni